PENGARUH AUDIT TENURE, DEBT DEFAULT, DAN OPINION SHOPPING TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA INDUSTRI TEKSTIL DAN GARMEN PERIODE TAHUN 2014-2018 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Osta Nababan, Benny; Maulidya, Karlina (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2021)
As global business competition is getting tougher, the company not only aims to seek optimal profit but also aims for the financial and non-financial survival of a company to be able to operate in the future. The conditions and events experienced by the company can provide an indication of the company's going concern, examples of significant and continuous losses that raise doubts about the company's survival. Going concern is the survival of a business entity and is an assumption in the financial reporting of the entity so that if the entity experiences the opposite condition the entity becomes a problem. This study aims to examine the relationship between audit tenure, debt default, and opinion shopping on going concern audit opinion acceptance. This study uses a sample of textile and garment companies listed on the Indonesia Stock Exchange for the period 2014-2018. Based on purposive sampling, a total sample of 16 companies. Hypothesis testing using logistic regression. The results showed that audit tenure, debt default, and opinion shopping had no significant effect on going concern audit opinion acceptance.